1981
DOI: 10.2136/sssaj1981.03615995004500050030x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Slow‐Release Nitrogen Sources on Baron Kentucky Bluegrass

Abstract: As new nitrogen (N) sources are introduced, it is important that they be evaluated and their release characteristics determined in order to provide us with a basis on which to make fertilizer recommendations. In this study, several N sources were evaluated for maintenance fertilization of Kentucky bluegrass (Poa pratensis L.) turf. Treatments included isobutylidene diurea (IBDU) materials of two particle‐size ranges, sulfur‐coated ureas (SCU) in two size ranges from Canadian Industries Limited (CIL), SCU from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…This frequent fertilization increases the time, effort, and dedication required to maintain a high quality lawn. Thus, controlled-release N sources, like SCU that do not rely on microbial degradation for N release, have been evaluated for their ability to produce a high quality turf (4,14,15,18,30). The newest group of controlled-release N sources is PCU but response data is limited and direct comparisons to SCU or urea in the same study is generally lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This frequent fertilization increases the time, effort, and dedication required to maintain a high quality lawn. Thus, controlled-release N sources, like SCU that do not rely on microbial degradation for N release, have been evaluated for their ability to produce a high quality turf (4,14,15,18,30). The newest group of controlled-release N sources is PCU but response data is limited and direct comparisons to SCU or urea in the same study is generally lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that KBG requires more N to sustain quality than PRG or TTTF (Christians, 2004). Since KBG is the most widely planted lawn species, the majority of research has been conducted using this species (Hanson and Juska, 1961;Hummel and Waddington, 1981;Starr and DeRoo, 1981;Jiang and Hull, 1998;Heckman et al, 2000) or KBG species mixtures (Kopp and Guillard, 2002). Much less information exists for PRG (Watson, 1987;Liu et al, 1993;Miltner et al, 2001;Engelsjord et al, 2004), or TTTF (Liu et al, 1993;Hall et al, 2003;Bigelow et al, 2005;Liu and Hull, 2006), which comprises a large portion of the lawns planted in the last decade.…”
mentioning
confidence: 99%
“…Some slow-release fertilizers may possess this characteristics and in several studies have been found to reduce or eliminate leaching losses of nutrients (Bredakis and Steckel 1963;Rieke and Ellis 1974;Brown et al 1982;Snyder et al 1984;Mancino 1991). In addition, lower risk of N loss by volatilization, less chances of fertilizer burn, fewer applications at higher rates and consequent economic saving, and a longer duration of N release, are among the several reported benefits of the slowrelease fertilizers (Hummel and Waddington 1981).…”
mentioning
confidence: 99%